A Multidimensional Assessment of Metacognition Across Domains in Multiple Sclerosis. (10th February 2021) - Mazancieux, Audrey; Moulin, Chris J.A.; Casez, Olivier; Souchay, Céline
Abstract: Objective: In neurological diseases, metacognitive judgements have been widely used in order to assess the degree of disease awareness. However, as yet little research of this type has focused on multiple sclerosis (MS). Method: We here focused on an investigation of item-by-item metacognitive predictions (using feeling-of-knowing judgements) in episodic and semantic memory and global metacognitive predictions in standard neuropsychological tests pertinent to MS (processing speed and verbal fluency). Twenty-seven relapsing–remitting MS (RR-MS) patients and 27 comparison participants took part. Results: We found that RR-MS patients were as accurate as the group of comparison participants on our episodic and semantic item-by-item judgements. However, for the global predictions, we found that the MS group initially overestimated their performance (ds = .64), but only on a task on which performance was also impaired (ds = .89; processing speed). We suggest that MS patients, under certain conditions, show inaccurate metacognitive knowledge. However, postdictions and item-by-item predictions indicate that online metacognitive processes are no different from participants without MS. Conclusion: We conclude that there is no monitoring deficit in RR-MS and as such these patients should benefit from adaptive strategies and symptom education.